(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Engineering design of furniture is an important issue for modern industry and it can be accomplished by means of creating a model structure and analyzing by a convenient software. A fair strength analysis of furniture structure is a computationally complex process since various types of member types, e.g. springs, upholster plates and complicated mechanisms type connections, are included in modelling. Finite element method (FEM) is the most convenient approach to analyze furniture systems because of the member variety and the furniture’s, in general, complex geometry. In this study, an improvable methodological approach was recommended for numerical analyses. Upholstered sofas are tested under backrest frame loads according to the principles of FNAE 80-214 General Services Administration Upholstered Furniture Test Method (GSA), then numerical analysis is carried out to simulate the performance tests on virtual platform. 3D modelling of sofa is made with SpaceClaim 3D solid models software and analyses are performed with a Finite Element Software, Ansys Workbench. Entire system of the sofa, including all members, joints, connections and springs are defined with convenient parameters related to mechanical properties of the material and the resulting deformations of the experiments. In this study, the sofa model is developed in a methodological manner, in three different ways. The model is improved with small details and it is observed that small changes in the model resulted in essential outcomes such that consistent results are decided to be achieved by means of tuning some parameters, e.g. spring constants, upholster thickness and elasticity. According to the results, reasonable estimates are obtained from the numerical analyses by using this methodological approach.